'It's one of those "It'll never happen to me" things': young women's constructions of smoking and risk. (18th August 2017) - Triandafilidis, Zoi; Ussher, Jane M; Perz, Janette; Huppatz, Kate
Abstract : In this article, we examine how young women make sense of the risks associated with smoking cigarettes. We recruited young women smokers and ex-smokers living in Australia in 2014 and 2015 to participate in semi-structured interviews and a participant-produced photography activity on young women's experiences of smoking and smoking-related risk. We analysed the data using discourse analysis to examine how young women positioned themselves in relation to smoking-related risk, and how this was shaped by discourses of health, risk and femininity. We identified four dominant interpretative repertoires: 'the risks of smoking are self-evident', 'it's not going to happen to me', 'smoking as a lesser evil' and 'smoking to cope with stress and emotion'. Through our analysis, we found that by drawing on these repertoires, participants were able to position the risks of smoking as both acceptable and unacceptable. Participants also made use of several of these repertoires to position anti-smoking messages as ineffective. We place these findings in the context of broader health and risk discourses surrounding young women's use of smoking to reinforce and subvert representations of 'respectable' femininity. We identify ways in which public health approaches could and should be developed to recognise the complexity and contradiction inherent in young women's lay accounts of smoking-related risk and situate smoking risks in the context of young women's everyday lives.